2018
DOI: 10.1002/ijgo.12561
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic floor dysfunction in the immediate puerperium, and 1 and 3 months after vaginal or cesarean delivery

Abstract: The type of delivery was not associated with differences in the short-term development of postpartum PFD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 27 publications
(56 reference statements)
0
13
1
3
Order By: Relevance
“…Therefore, the size of the genital hiatus can predict the occurrence of POP over time (12). This finding contradicts previous reports that in the immediate postpartum period, the delivery mode only significantly influences the measurement of POP-Q point C (7).…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Therefore, the size of the genital hiatus can predict the occurrence of POP over time (12). This finding contradicts previous reports that in the immediate postpartum period, the delivery mode only significantly influences the measurement of POP-Q point C (7).…”
Section: Discussioncontrasting
confidence: 58%
“…During pregnancy, delivery, and the puerperium, women experience hormonal and physical changes, and the resulting stress on the pelvic floor can cause PFD (5,6). However, in a recent study, the authors concluded that the mode of delivery is not correlated with variations in the short-term development of postpartum PFD (7). So far, the effects of delivery mode on pelvic floor function have remained controversial.…”
Section: Introductionmentioning
confidence: 99%
“…SERPINA5 is usually present in urine in very low concentrations and serves, among other functions, as a pro-inflammatory factor, which might be an explanation for it overexpression in samples of patients with SUI [1,[14][15][16][17][18][19][20]. Furthermore, SERPINA5 was recently mentioned in a number of publications addressing diverse medical conditions, including pediatric leukemia, breast cancer, HIV infection, and hepatocellular carcinoma, which have identified a role played by SERPINA5 during disease development [21][22][23][24].…”
Section: Proteins Identifiedmentioning
confidence: 99%
“…It is often reflected in the control through the adoption of mechanisms of discipline, the discomfort of women when they look or touch their own body, especially the genitalia, placing this act as immoral, interfering directly in the knowledge of the same about their own body, since they feel constrained by feelings of curiosity about themselves. 16 It is considered that there is a difficulty for women to look at their own vagina, especially when they undergo traumatic deliveries and/or receive suture on the pelvic floor, 17 as was the case with one of the interviewees, who places the points as potentialisers of this difficulty. It is explained that these points in the perineal region can often result from episiotomy, a surgical incision in the perineum for the passage of the fetus at the time of delivery, whereas the perineal laceration consists of an unintentional rupture of this structure and, in its vast majority, are simple lacerations that do not cause so much damage and suffering for women.…”
Section: Researched the Internet And Had A Class At School So I Almentioning
confidence: 99%
“…It is explained that these points in the perineal region can often result from episiotomy, a surgical incision in the perineum for the passage of the fetus at the time of delivery, whereas the perineal laceration consists of an unintentional rupture of this structure and, in its vast majority, are simple lacerations that do not cause so much damage and suffering for women. The new guidelines and good practices of childbirth care of the Ministry of Health 17 have increasingly discouraged the performance of episiotomy, but this is still a recurrent practice in health services. 18 The women in this study were reported to have intact perineum and spontaneous lacerations of first or second degree.…”
Section: Researched the Internet And Had A Class At School So I Almentioning
confidence: 99%